A 1-V 0.25- $μ \textW$ Inverter Stacking Amplifier With 1.07 Noise Efficiency Factor - Shen, Linxiao; Lu, Nanshu; Sun, Nan (IEEE Journal of Solid-State Circuits, 2018)
This paper presents a highly power-efficient amplifier. By stacking inverters and splitting the capacitor feedback network, the proposed amplifier achieves six-time current reuse, thereby significantly boosting the transconductance and lowering noise but without increasing the current consumption. A novel biasing scheme is devised to ensure robust operation under 1-V supply. A prototype in 180-nm CMOS has 5.5-μVrms noise within 10-kHz BW while consuming only 0.25-μW power, leading to a noise efficiency factor of 1.07, which is the best among reported amplifiers.